Influential Factors Analysis of ICAO English Proficiency Level of Air Traffic Controllers (ATC) Officers in Makassar - Mardiani Mardiani (Dinasti Publisher, 2024)
The rapid development of instant lifestyles has significantly impacted the air transportation system. The air transportation system involves many parties, for example, facilities, infrastructure, and human resources. One of the parties that plays important role in human resources is the Air Traffic Controller (ATC). ATC playing a crucial role in coordinating air traffic and providing assistance to pilots. By seeing the importance of an ATC's duties, particularly in communicating with pilots, which requires them to use English as an international language in the world of flight, this research sought to identify the factors influencing the English language proficiency of ATC Officers at Sultan Hasanuddin Makassar International Airport. The research used interviews, documentation, and data analysis methods to gather and analyze data. The research's findings demonstrated that factors influencing the English language proficiency of ATC Officers at Sultan Hasanuddin Makassar International Airport are: a. Writing skills: 1) interest factors and 2) environmental factors. b. Listening skill: 1) interest factor. 2) vocabulary factor; 3) concentration factor; and 4) interest in the topic factor. c. Speaking Skill: 1) psychological factors and 2) grammatical factors. d. Reading Skill: 1) motivational factors. 2) language complexity factor; and 3) vocabulary factor.